THE FACTORS AFFECTING TO PEOPLE ON FISH CONSUMPTION IN DISTRICT RUMBAI PESISIR PEKANBARU RIAU PROVINCE - Riawa, Arga Oxa; Yulinda, Eni; ', Darwis (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in October 2016 which is housed in the District Rumbai Pesisir, Pekanbaru in Riau Province. The method used in this study is a survey method. Of the respondents in this study amounted to 89 people. Based on the research that has been conducted on the level of consumption of fresh fish in the District Rumbai Pesisir using multiple linear analysis a number of conclusions, namely the level of fresh fish consumption was 18 kg / capita / year. The influence of independent variables such as family income, number of family members, the price of chicken and regions of origin there is significant influence. These factors affect up to 48.0%, while the remaining 52.0% are variable factors beyond research.Keywords :Consumption, Fish Fresh